Simulating shot peening based on a dislocation density-based model with a novel time integration algorithm - Ren, FeiHu; Zhao, MingHao; Lu, Chunsheng; Zhang, JianWei; Wang, BingBing (International journal of solids and structures, 2024)
•A novel time integration algorithm is proposed for a dislocation density-based model.•The coupling of microscopic dislocation density and macroscopic plasticity is guaranteed in the model.•The proposed method is superior to the existing two-level iteration method.•The influence of shot peening parameters is clarified on grain refinement. Shot peening has been widely used in processing various components since it can bring in residual compressive stress and effectively refine the grain size of impacted area. To simulate grain refinement induced by shot peening, the dislocation density-based model has recently been introduced, however, the existing time integration algorithm is not stable and usually leads to divergent solutions in iterations. In this paper, a novel time integration algorithm is proposed for the dislocation density-based model. Based upon the algorithm, numerical studies on multi-shot AISI4340 steel are carried out with different coverages, velocities, shot diameters, and peening angles. It is shown that the method converges faster than the two-level iteration method, and the predicted dislocation cell structure sizes after shooting are consistent with experimental results. Besides that, increasing coverage can refine the size of a dislocation cell, which is closely dependent on the shot diameter, impact velocity, and angle. Thus, to achieve the desired grain size or the depth of refinement, it is necessary to take the shot diameter and velocity into account simultaneously.